PERAN EKSPOR, NILAI TUKAR DAN TINGKAT BUNGA TERHADAP JUMLAH CADANGAN DEVISA DI INDONESIA - Baihaqi Alfathony (2022)
The limited amount of foreign exchange reserves owned by Indonesia is still one of the problems faced today. Foreign exchange reserves will also continue to experience changes due to macroeconomic factors such as exports, exchange rates and interest rates. This study aims to determine the role of exports, exchange rates and interest rates on the amount of foreign exchange reserves in Indonesia. The regression of this study used multiple linear regression with the Ordinary Least Square (OLS) method and quantitative descriptive analysis. The data used is secondary data with a time series or time series from 1988-2020 with a total of 33 observations. The data is processed using software eviews 10. The results of this study indicate that partially (1) exports have a significant positive effect on the amount of foreign exchange reserves in Indonesia (2) the exchange rate has a significant positive effect on the amount of foreign exchange reserves in Indonesia (3) the interest rate has a significant negative effect on the amount of foreign exchange reserves in Indonesia, while simultaneously or simultaneously exports, the exchange rate and the interest rate affect the amount of foreign exchange reserves in Indonesia. Keywords: Foreign Exchange Reserves, Exports, Exchange Rates, Interest Rates